Development of Web-Based Interactive Learning Media on Lines and Angles Material in 7th grade of Junior High School - Vina Novianti; Dwi Priyo Utomo; Mayang Dintarini (MEJ (Mathematics Education Journal), 2019)
This research aimed at: 1) analyzing and describing the development of web-based interactive learning media, 2) analyzing and describing the effectiveness of web-based interactive learning media. The approach of this research was descriptive quantitative. The subjects of this research were the students of 7th grade of Junior High School. The instruments that used were the validation sheets of media and material experts, students’ response questionnaires, and test. The data analysis was done by calculating the score of each indicator to find out the validity, students’ responses, and the students’ learning outcomes.  Based on the validation result that obtained from the analysis of media validation, it was obtained the averages of 3,56 and it was very valid and the result of material validation analysis obtained the averages of 3,29 that meant valid. Therefore, the learning media was stated as proper to be tested.  However, the analysis result of students’ response analysis was obtained the averages of 87%, in which the learning media got very good response both of students and the students’ learning outcomes that showed the percentages of students achieved the KKM (Minimum Completeness Criteria) in the score of 75 as much as 100% with a very high criterion. Therefore, the web-based interactive learning media was stated as effective and could be used in the learning process.